The Role of Credit Risk as Mediating the Effect of Liquidity on Sharia Banking Performance - Julia Safitri; Yuridistya Primadhita (Perisai : Islamic Banking and Finance Journal, 2022)
This study aims to examine and analyze the relationship of the influence of liquidity on bank performance mediated by credit risk. Using data on Islamic banking companies listed on the IDX in 2013-2019. The methodology of this research was carried out to achieve the objectives of this study, namely how the influence of liquidity on the performance of Islamic banking companies in Indonesia which is mediated by credit risk. By processing data from data collected from the pre-pandemic and during the pandemic, this research can prove the proposed hypothesis. The analytical tool used is SEM-PLS with WarpPLS 7.0 application. The results of this study indicate that credit risk can partially mediate the relationship between the influence of liquidity on bank performance. This study succeeded in proving that the influence of liquidity on bank performance is acceptable and can be mediated by credit risk. This is in line with the Commercial Loan Theory which explains that providing loans to short-term and productive customers can minimize customer defaults, so that the company's performance will be maintained. During the current pandemic, it is one of the things that makes companies careful in managing liquidity as well as in distributing credit. Banks must be really selective in choosing loans submitted by customers, in order to avoid defaults that cause a decline in bank performance.